Effect of utilisation of nano POFA on performance of self-consolidating high-performance concrete (SCHPC) / Nuradila Izzaty Halim ...[et al.] - Newman, Aidan; Muhd Sidek, Muhd Norhasri; Mohd Saman, Hamidah; Suliman, Nurul Huda (Universiti Teknologi MARA, 2021)
Malaysia's palm oil industry plays a significant role in the country's economy. However, a large amount of palm oil fuel ash (POFA), a by-product of this industry, may negatively affect the environment and human health. Hence, this study hypothesized that POFA might be re-used in the form of replacement in concrete to lessen the risk to the environment or human health. Self-consolidating high-performance concrete (SCHPC) has been innovating progressively over the years. In this paper, SCHPC is innovated by utilizing nano POFA (NaPOFA) to improve its performance. The POFA performance greatly improved when the particle size is reduced because the finer forms of POFA react effectively with the other constituent materials to produce stronger concrete. Hence this paper presents the experiment of the effect of utilization of NaPOFA as a replacement to cement ranging between 0% and 10% to produce a self-consolidating high-performance concrete with good workability. The tests conducted were the flow table and compression test. The specimen used in the compression tests were 50 mm concrete cubes, tested in 1, 3, 7, 14, and 28 days. It was found that the inclusion of 1% POFA as a replacement to cement in concrete produced the highest compressive strength, 73.31 MPa, on the 28th day of testing. It was also found that its workability was as good as the control concrete. Thus, the utilization of POFA could be considered environmental-friendly since it can be used as cement replacement and enhance the performance in terms of workability and strength.